Wi-Fi advancements and the potential use of Wi-Fi 7 in crisis situations - Komarac, Boris; Grgić, Mario; Janeš, Hrvoje (Crisis Management Days, 2025)
This paper explores the IEEE 802.11be standard, also known as Wi-Fi 7 Extremely High Throughput (EHT), the latest iteration of Wi-Fi technology. Comparing it to its predecessors to highlight the significant technical and performance differences, with a focus on the capabilities and advantages compared to 802.11ax, upon which it is built. The analysis includes improvements in transfer speeds, energy efficiency and network capacity particularly through the enhanced use of Multi-User MIMO (MU-MIMO), which allows simultaneous communication with multiple devices, increasing overall network efficiency and performance. Additionally, it discusses the Multi-Link Operation (MLO) technology, which enhances connectivity by allowing devices to maintain multiple simultaneous connections across different channels and bands. It also introduces the Multi Resource Units (MRU) technology which represents an advanced technology that enables more efficient use of radio resources in wireless networks. Furthermore, it examines the potential application of Wi-Fi technology in crisis situations, such as natural disasters, emphasizing its role in ensuring reliable communication and connectivity. Through an in-depth analysis of technical specifications this paper provides insight into the possibilities and challenges in implementing Wi-Fi 7 technology, considering its security aspects and its ability to address challenges in crisis scenarios.